BAGAIMANA HUBUNGAN PERASAAN LELAH KERJA PADA KINERJA KARYAWAN PT BARITO GALANGAN NUSANTARA - Hidayat, Ilham; Efrianti, Kumara; Lamsah, Lamsah (Servqual: Jurnal Ilmu Manajemen, 2025)
This study aims to analyse workload, work fatigue, and their impact on employee performance at PT Barito Galangan Nusantara. The workload at this company has a complex characteristic that includes not only the quantity of work but also the technical difficulty level, project deadline accuracy, and challenging environmental conditions such as harsh weather around the Barito River area. The research method used is qualitative descriptive with data collected through in-depth interviews with informants representing various job levels, including managers, HRD, operational supervisors, and field operators. The results show that the high workload and uneven distribution of tasks, especially to experienced and specialized employees, significantly contribute to prolonged work fatigue. The on-call system and frequent emergency calls exacerbate the condition, potentially lowering employee performance. Although the company has implemented several mechanisms, including an early warning system and periodic workload evaluations, challenges in workload redistribution remain, particularly when facing sudden orders and intensive overtime needs. This study emphasizes the importance of effective workload management to minimize work fatigue and maintain employee performance. Additionally, the active role of the HR department in monitoring employee conditions and taking anticipatory actions is crucial to improving operational effectiveness and worker well-being in the shipyard industry.